Barokah Sebagai Karakteristik Perekonomian Islam - M. Alaika Nasrulloh (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2019)
So many aspects of life are explained by al-hadith, including the aspects of Islamic economics. among them are about baraka or blessing of property, which are the characteristics of the Islamic economy. This type of research is a research library research, with primary data sources are hadiths that are in the al-Bukhari saheeh book and supported by secondary data sources that come from books or literature relevant to the study theme. Data collection techniques using documentation, while the analytical method using descriptive analysis of takhrij hadith which originates from the analysis of the quality of matan and the traditions of the hadith. By searching for the keyword lafadz ÙŠØ¨Ø§Ø±Ùƒ (yubarak - blessed), the hadith found related to economic barriers are: Hadith al-Bukhari index number 5960, 2910, 1338, 1379, 2545. After analyzing the sanad and matan, it is known that the Hadith with the theme of wealth blessing with index 5960 in the book of Saheeh al-Bukhari is the quality of saheeh, maqbul and ma'mul bih; The blessing of property should be a top priority in the economic behavior of Muslims, this is a characteristic of the Islamic economy that cannot be ignored; Some ways to get blessings in property are with a strong belief that only Allah can provide sufficiency (not much wealth), obtain property with good business, lawful and not from begging.